Incidence of spontaneous intracranial hypotension in a community: Beverly Hills, California, 2006–2020. (April 2022) - Schievink, Wouter I; Maya, M Marcel; Moser, Franklin G; Simon, Paul; Nuño, Miriam
Abstract: Background: Spontaneous intracranial hypotension is diagnosed with an increasing frequency, but epidemiologic data are scarce. The aim of this study was to determine the incidence rate of spontaneous intracranial hypotension in a defined population. Methods: Using a prospectively maintained registry, all patients with spontaneous intracranial hypotension residing in Beverly Hills, California, evaluated at our Medical Center between 2006 and 2020 were identified in this population-based incidence study. Our Medical Center is a quaternary referral center for spontaneous intracranial hypotension and is located within 1.5 miles from downtown Beverly Hills. Results: A total of 19 patients with spontaneous intracranial hypotension were identified. There were 12 women and seven men with a mean age of 54.5 years (range, 28 to 88 years). The average annual incidence rate for all ages was 3.7 per 100, 000 population (95% confidence interval [CI]: 2.0 to 5.3), 4.3 per 100, 000 for women (95% CI, 1.9 to 6.7) and 2.9 per 100, 000 population for men (95% CI, 0.8 to 5.1). Conclusion: This study, for the first time, provides incidence rates for spontaneous intracranial hypotension in a defined population.